Modeling group and individual learning: lessons for integrating disciplines and agile research. (18th June 2019) - Anderson, Edward G.; Lewis, Kyle
Abstract: We discuss the genesis of the paper for which the 2018 Forrester Award has been given. We then summarize its findings and put it into the context of the research streams in which it is embedded. We also describe the effects of the award paper on subsequent research. We then briefly discuss how laboratory experiment, field, and modeling work can complement each other in social systems research. Finally, we present some thoughts for leveraging the expertise of researchers and audiences from outside domains to the field of system dynamics, based on lessons from our work together as co‐authors and our mutual experience in project management, particularly in agile software development techniques. © 2019 System Dynamics Society